"Cryptic" diagenesis and its implications for speleothem geochronologies. (15th September 2016) - Bajo, Petra; Hellstrom, John; Frisia, Silvia; Drysdale, Russell; Black, Jay; Woodhead, Jon; Borsato, Andrea; Zanchetta, Giovanni; Wallace, Malcolm W.; Regattieri, Eleonora; Haese, Ralf
Abstract: Speleothems are usually considered as one of the most amenable palaeoclimate archives for U-series dating. A number of studies in recent years, however, report cases of diagenetic alteration which compromises the use of U-series systematics in speleothems, resulting in inaccurate U-Th ages. Here we present the results of a high-resolution U-Th dating study of a stalagmite (CC26) from Corchia Cave in Italy where we document a number of departures from an otherwise well-defined age-depth model, and explore potential causes for these outliers. Unlike examples illustrated in previous studies, CC26 contains no visible evidence of neomorphism, and appears, at least superficially, ideally suited to dating. Good reproducibility obtained between multi-aliquot U-Th analyses removes any possibility of analytical issues contributing to these outliers. Furthermore, replicate analyses of samples from the same stratigraphic layer yielded ages in stratigraphic sequence, implying very localized open-system behavior. Uranium loss is suggested as a causative mechanism on account of the fact that all the outliers are older than their assumed true age. A limited number of micro-voids were observed under micro-CT analyses, and it is proposed that these were pathways for U loss. Uranium-loss modelling allows us to constrain the possible timing of diagenetic alteration and indicates that the precursor for the outlier with the largest age discrepancy (309%) must have been aragonite. This study indicates that visibly unaltered speleothems may still contain small domains that have experienced post-depositional alteration. Such "cryptic" diagenesis, as recorded in this stalagmite, has implications for the constancy of accuracy of the U-series dating technique, and suggests a need for careful examination of speleothems prior to dating, particularly in low-resolution U-Th studies. Highlights: Isolated domains in apparently pristine speleothems can show open system behavior. "Cryptic" diagenesis with very localized U-loss is observed in a Holocene speleothem. Misinterpretation of U-Th age estimates in such samples can only be eliminated based on multi-aliquot age determinations. Micro-CT scans recorded a limited number of voids in otherwise dense speleothem.